A Comparison of BREAST-Q Scores between Prepectoral and Subpectoral Direct-to-Implant Breast Reconstruction. (29th November 2021) - Le, Nicole K.; Persing, Sarah; Dinis, Jacob; Gabrick, Kyle S.; Wu, Robin T.; Sinnott, Catherine J.; Avraham, Tomer; Young, Anke Ott; Alperovich, Michael
Abstract : Background: Subpectoral breast implant placement has in recent history predominated in breast reconstruction, but there has been more recent adoption of prepectoral implant reconstruction. There has been limited study to date of patient-reported outcomes comparing the two techniques. Methods: Patients who underwent direct-to-implant breast reconstruction between 2013 and 2018 were included in this retrospective cohort study. Eligible patients were asked to complete BREAST-Q domains comparing quality of life and satisfaction. Descriptive, t test, chi-square test, and multivariate linear regression analyses were performed to compare BREAST-Q scores. Significance was defined as p ≤ 0.05. Results: There were 64 patients (114 breasts) who underwent prepectoral reconstruction and 37 patients (68 breasts) who underwent subpectoral reconstruction. Among the 101 women (182 breasts), there were no significant differences between BREAST-Q scores and implant position for the Satisfaction with Breasts domain (adjusted p = 0.819), Psychosocial Well-being domain (adjusted p = 0.206), or Physical Well-being Chest domain (adjusted p = 0.110). The subpectoral implant cohort was associated with higher scores, 53 versus 47, for the Sexual Well-being module (adjusted p = 0.001). Conclusions: Patients undergoing direct-to-implant breast reconstruction had comparable BREAST-Q satisfaction scores for most modules regardless of implant plane. The subpectoral implant cohort scored higher for sexual well-being.